Leaning against the global financial cycle - Andrea Ferrero; Maurizio Michael Habib; Livio Stracca; Fabrizio Venditti (European Central Bank (ECB), 2022)
We study the role and the interaction of the quality of institutions and of counter-cyclical policies in leaning against the Global Financial Cycle (GFC) in Emerging Economies (EMEs). We show that heteroegeneity in institutional strength is a key determinant of the different effects of the GFC on EME domestic financial conditions. Institutional strength also shapes the response in terms of counter-cyclical policies to sudden changes in global financial conditions as well as the effectiveness of such policies. We illustrate in a simple stylised model that countries may in fact decide to undertake ex ante costly structural reforms that reduce their vulnerability to the GFC or react ex post to the financial s hock. However, we also find that the Covid-19 episode seems to deviate somewhat from the general pattern of EME reaction to shifts in the GFC.
Keywords: F32; F38; E52; G28; 330; Global Financial Cycle; monetary policy; macro-prudential policies; foreign-exchange intervention; capital controls; emerging markets; institutions